2022
DOI: 10.3390/v15010104
|View full text |Cite
|
Sign up to set email alerts
|

A Counterintuitive Neutrophil-Mediated Pattern in COVID-19 Patients Revealed through Transcriptomics Analysis

Abstract: The COVID-19 pandemic has persisted for almost three years. However, the mechanisms linked to the SARS-CoV-2 effect on tissues and disease severity have not been fully elucidated. Since the onset of the pandemic, a plethora of high-throughput data related to the host transcriptional response to SARS-CoV-2 infections has been generated. To this end, the aim of this study was to assess the effect of SARS-CoV-2 infections on circulating and organ tissue immune responses. We profited from the publicly accessible g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 87 publications
2
2
0
Order By: Relevance
“…Over-expression of the cytokine IL6 has been reported to be highly associated with the mortality risk of COVID-19; IL6 also acts as a perpetrator of the SARS-CoV-2-induced cytokine storm [65][66][67] . However, IL6 appears to be down-regulated in the blood of COVID-19 patients (Figure 3), consistent with the findings of a previous bioinformatics study by Özbek and colleagues (2023), wherein IL6 was not found to be significantly dysregulated in diverse SARS-CoV-2-infected tissues 55 . This is probably due to the dual role of IL6 as a pro-and antiinflammatory cytokine [68][69] , as well as the diverse immune response patterns observed in COVID-19 patients 55,70 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Over-expression of the cytokine IL6 has been reported to be highly associated with the mortality risk of COVID-19; IL6 also acts as a perpetrator of the SARS-CoV-2-induced cytokine storm [65][66][67] . However, IL6 appears to be down-regulated in the blood of COVID-19 patients (Figure 3), consistent with the findings of a previous bioinformatics study by Özbek and colleagues (2023), wherein IL6 was not found to be significantly dysregulated in diverse SARS-CoV-2-infected tissues 55 . This is probably due to the dual role of IL6 as a pro-and antiinflammatory cytokine [68][69] , as well as the diverse immune response patterns observed in COVID-19 patients 55,70 .…”
Section: Discussionsupporting
confidence: 90%
“…However, IL6 appears to be down-regulated in the blood of COVID-19 patients (Figure 3), consistent with the findings of a previous bioinformatics study by Özbek and colleagues (2023), wherein IL6 was not found to be significantly dysregulated in diverse SARS-CoV-2-infected tissues 55 . This is probably due to the dual role of IL6 as a pro-and antiinflammatory cytokine [68][69] , as well as the diverse immune response patterns observed in COVID-19 patients 55,70 . The pleiotropic anti-inflammatory cytokine IL4 71 is also down-regulated in COVID-19 blood samples (Figure 3), in agreement with previous studies suggesting cytokine storm suppression during SARS-CoV-2 infection 55,56 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations